Training and Mentoring of Health Cadres with the Smart Cadre Pocket Book to Prevent Stunting in Donggala Regency, Central Sulawesi - Taqwin, Taqwin; Nasrul; Amir; Lisnawati; Selvi Alfrida Mangundap; Rina Tampake; Sri Restu Tempali (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2025)
Stunting remains a significant public health problem in Indonesia, particularly in Donggala District, where the prevalence has reached 32.4%. In Loli Tasiburi Village, the prevalence of stunted children under five is 28%, exceeding the national average. Local government efforts through supplementary feeding have not been sufficient to reduce the prevalence, thus requiring additional interventions such as education and cadre empowerment. This community service activity aimed to improve the knowledge and skills of village cadres in stunting prevention through Training based on the Pocket Book for Smart Cadres to Prevent Stunting. The methods included interactive education, hands-on anthropometric measurement practice, pocket book distribution, and one-month mentoring. Evaluation was done through pre-test and post-test, skills observation, and post-training monitoring. The results showed a significant increase in cadre knowledge, with the average score rising from 58.5 to 84.2 (an increase of 43.9%), and 85% of participants could perform anthropometric measurements according to WHO standards. Post-training mentoring reinforced the cadres’ ability to apply their skills in community health posts, as indicated by the increased reports of early stunting detection and nutrition education for pregnant women and toddlers. The pocket book proved effective as a practical guide supporting program sustainability. This activity successfully enhanced cadre capacity in stunting prevention, although program continuity requires multi-sectoral support from village government, health centers, and local health authorities.